Cultivation and Enabling Effects of Social Support and Self-Efficacy in Parent–Child Dyads. Issue 12 (27th March 2021) - Banik, Anna; Zarychta, Karolina; Knoll, Nina; Luszczynska, Aleksandra
Abstract: Background: There are two alternative mechanisms, elucidating the reciprocal relationship between self-efficacy and social support when explaining health outcomes: self-efficacy beliefs may operate as the establisher of social support ( the cultivation model ) or social support may enable the formation of self-efficacy beliefs ( the enabling model ). Purpose: In line with the cultivation hypothesis, it was tested if self-efficacy (measured in parents and children) would indirectly predict parental and child moderate-to-vigorous physical activity (MVPA), via the mediator, social support (parent-provided, child-received). In line with the enabling hypothesis, it was tested if social support would predict MVPA indirectly, via the mediator, self-efficacy. Methods: A total of 879 parent–child dyads (1758 individuals; 52.4% girls, aged 5–11 years old, 83.2% mothers) provided self-reports at the baseline (T1) and the 7- to 8-month follow-up (T2). Body weight and height were measured objectively. Manifest path analyses were performed, controlling for the baseline levels of the mediator and dependent variables. Results: A similar number of significant simple indirect effects was found for the cultivation and the enabling model. Across the models, the indirect effects followed similar patterns: (a) within-individual indirect effects in children; (b) across-individual indirect effects, with the independent variable measured in children and the mediator/dependent variables measured in parents (e.g., child self-efficacy predicted parental support provision and, indirectly, parental MVPA); (c) across-individual indirect effects, accounting for self-efficacy and MVPA measured in children, combined with parental reports of social support. Conclusions: The findings provide support for both cultivation and enabling models in the context of MVPA among parent–child dyads. Abstract : Within-individual and across-individual effects of parental support provision and self-efficacy and child's support receipt and self-efficacy explain parental and child's physical activity at 7-8-month follow-up.